2018
DOI: 10.1017/bap.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

Industry type and environmental policy: Industry characteristics shape the potential for policymaking success in energy and the environment

Abstract: When can complex multi-round environmental policymaking like that seen in climate be successful? An emerging branch of literature examines how sequencing matters to success and under what circumstances path dependent dynamics can lead to increasingly stringent climate and environmental policy. Here, I propose an industry typology that divides industry into four categories based on their relationship and likely response to early regulatory policy moves. I use a series of case studies that compare the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…When costs and regulatory pressure are high, firms are expected to 'hedge'-seek to reduce their compliance costs, especially relative to competitors. Kelsey (2018) focuses on what firms produce as the driving force behind their material interests. Low-carbon producers are climate policy 'winners' and expected to be supportive, while carbon-intensive producers are 'losers' and expected to oppose policy.…”
Section: Firm Behaviormentioning
confidence: 99%
“…When costs and regulatory pressure are high, firms are expected to 'hedge'-seek to reduce their compliance costs, especially relative to competitors. Kelsey (2018) focuses on what firms produce as the driving force behind their material interests. Low-carbon producers are climate policy 'winners' and expected to be supportive, while carbon-intensive producers are 'losers' and expected to oppose policy.…”
Section: Firm Behaviormentioning
confidence: 99%
“…We have shown that incumbent business interests are not static but subject to change as a result of shifting technological, market, and policy conditions. The possible reinvention of Big Oil as a Big Gas industry also speaks to the question of whether polluters are not simply losers but "convertibles" (Kelsey 2018) that can be recruited to coalitions in support of low-carbon transitions (Roberts et al 2018). However, there may be negative consequences and costs associated with such recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The second group is producers: industrial actors who produce carbon-intensive goods and services and will therefore bear the costs of policies that aim to reduce carbon pollution. To be sure, a number of different types of firms fall into this category (Kelsey 2018) and their preferences will vary (Colgan et al, 2020;Cory et al, 2020;Downie, 2017;Genovese & Tvinnereim, 2019;Meckling, 2015). However, again for parsimony, I refer broadly to all emissions-intensive firms as "cost-bearing".…”
Section: Climate Change Policy As Long-term Policy Investmentmentioning
confidence: 99%